Rancang Bangun Alat Pengiris Bawang Serbaguna - Zulkarnaen, Amay Velda; Dabet, Abubakar; Yusuf, Muhammad; Putra, Reza; Jumadi, J (Malikussaleh Journal of Mechanical Science and Technology, 2023)
This study aims to obtain the production amount of the slicing process of a multipurpose onion slicer according to the needs of the home industry. This versatile onion slicer uses two ways, namely conventional and unconventional. From the experimental results, the rotation of the cutting disk obtained a speed of 46.05 m / s, the cutting power obtained based on the calculation of 513.9 Watt, smaller than the motor power used. The average working capacity of slicing using an electric motor within 1 hour for shallots, plantains, and cassava is 213 g/min, 590.33 g/min and 474.66 g/min, respectively. While if using the manual method is 125.66 g/min, 128.66 g/min, and 161 g/min. Using a 220 Volt water pump drive engine 0.5 HP 2000 Rpm, which is added to the dimmer to adjust the rotation speed. The frame uses Aluminum with a thickness of 1.2 mm.